PENGARUH BAHASA ARAB TERHADAP PERKEMBANGAN BAHASA INDONESIA - Pantu, Ayuba (ULUL ALBAB Jurnal Studi Islam, 2014)
This study aims to discover and describe how the Arabic influence on the development of the Indonesian language,  which focused on the influence of the vocabulary,  the influence of the Arabic alphabet and its influences on Indonesian syntax,  as well as to discover how changes are absorbed Arabic vocabulary into Indonesian. The method used in this study is a literature review using the technique of content analysis,  which is a research technique for making inferences that can be replicable,  and valid the data by looking at the context. Sources of data in this study are the books relating to the object of research,  among Indonesian Dictionary and other books. The results showed that the effect of Indonesian Arabic is big enough. This can be seen in the uptake of the Arabic word which ranks third after Dutch and English 1, 495 words. In addition,  the use of Arabic script in Indonesian,  which until now still many books,  both Islamic religious books,  Arabic books,  tales,  literature,  written in Arabic alphabet Malay. Arabic influence on Indonesian syntax can be seen in books or Qur’an translations. The words of the absorption Arabic generally undergo changes in shape,  as adapted to the Indonesian grammar or phonemes. It also changes the meaning,  although the numbers are limited.